MVACC / Nur Wahida Mohamad Yahya and Norarifah Ali - Mohamad Yahya, Nur Wahida; Ali, Norarifah (Faculty of Art and Design, 2021)
The world now facing a phase when they need to be careful when they going outside. This all happened beacause of the Pandemic Covid-19 that effect all country around the world. There will be no contact like hand shake or hug when we came across our friends. Every person in all kind of generations must follow new norm that state by the government to avoid getting infection by this dangerous virus. Everyone needs to learn and practice social distancing when they go out. And the main things that people need to do is wearing a mask everytime they come out fom the house. Mask become a must to protect ourself from the infection, for example when we speak to people outside, we never know they already infected or not, so by wearing a mask it help prevented the virus from infected exposed place of our body which is face. The virus will damage our respiratory tract, that is why mask are always needed. Even though people following the new norm, there is still a problems that arise and can not be avoided . This lead into lots of problems that occur solutions. When collecting the research about this pandemic, designer found a problem that can be overcome by designing a new product.